Scale Validation and Impact of Program Difficulty and Study Habits on Performance among Undergraduate Pharmacy Students - Ehidiamen Oamen, Theophilus; Jegede, Ayodapo Oluwadare; Oluwatomisin Irenitemi, Enitan (Universitas Negeri Semarang, 2024)
Study habits and program difficulty in the context of academic performance are critical considerations among undergraduate pharmacy students. However, a robust, validated measurement instrument is absent to evaluate the relationship between study habits, program difficulty, and academic performance from students' perspectives. 352 undergraduate pharmacy students [19555%) females and 157 (45%) males] from 3 public Universities in Nigeria were surveyed. Structural equation modeling was used to develop and test the model validity using exploratory and confirmatory factor analysis (EFA and CFA). EFA extracted a three-factor structure aligned with the theorized framework. CFA revealed adequate model fit and construct validity. Measurement invariance analysis showed configural, metric, scalar, and residual invariance by gender, age, class, and University. Study habits positively influenced students' performance while program difficulty had a negative impact. We propose a robust, validated instrument-program difficulty, study habits, and academic performance scale useful for academicians, educational and curriculum managers",